2019
DOI: 10.3390/plants8120602
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Abiotic Stress Conditions on Expression of Calmodulin (CaM) and Calmodulin-Like (CML) Genes in Wild-Growing Grapevine Vitis amurensis

Abstract: Plant calmodulins (CaMs) and calmodulin-like proteins (CMLs) are important plant Ca2+-binding proteins that sense and decode changes in the intracellular Ca2+ concentration arising in response to environmental stimuli. Protein Ca2+ sensors are presented by complex gene families in plants and perform diverse biological functions. In this study, we cloned, sequenced, and characterized three CaM and 54 CML mRNA transcripts of Vitis amurensis Rupr., a wild-growing grapevine with a remarkable stress tolerance. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…CML protein belongs to calcium-binding EF-hand family proteins, which play an important role in cellular calcium signalling cascades through the regulation of numerous target proteins (Ranty et al 2006;Shi and Du 2020). This protein has a role in salinity tolerance and genes related to CML are shown to be upregulated under salt stress (Zeng et al 2015;Dubrovina et al 2019;Shi and Du 2020) and has improved the salt tolerance of Arabidopsis by affecting abscisic acid mediated pathways (Magnan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…CML protein belongs to calcium-binding EF-hand family proteins, which play an important role in cellular calcium signalling cascades through the regulation of numerous target proteins (Ranty et al 2006;Shi and Du 2020). This protein has a role in salinity tolerance and genes related to CML are shown to be upregulated under salt stress (Zeng et al 2015;Dubrovina et al 2019;Shi and Du 2020) and has improved the salt tolerance of Arabidopsis by affecting abscisic acid mediated pathways (Magnan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…CMLs are a unique class of EF-hand proteins and specifically existed in plants. The CML gene family has been characterized in some plant species, such as Arabidopsis [ 9 ], rice [ 10 ], grapevine ( Vitis amurensis ) [ 11 ], Chinese cabbage (Brassica rapa) [ 12 ] and tomato ( Solanum lycopersicum ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were 50 and 32 CML genes in Arabidopsis and rice, respectively [ 22 , 42 ]. CML genes were recently also identified in tomato, Medicago, grapevine, and apple [ 33 , 43 , 44 , 45 , 46 , 47 ]. MpCML40 is the first CML gene identified in Pongamia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Arabidopsis and rice, several studies showed that CMLs in other plants were also involved in abiotic stress signaling. Expression of 32 CML genes in wild-growing grapevine ( Vitis amurensis ) was shown to be responsive to abiotic stresses, including drought, salt, heat, and cold [ 33 ]. In Glycine soja , GsCML27 participated in salt and osmotic stresses [ 34 ].…”
Section: Introductionmentioning
confidence: 99%